Astragalus polysaccharides alleviates lipopolysaccharides-induced inflammatory lung injury by altering intestinal microbiota in mice - Ming, Ke; Zhuang, Shen; Ma, Ning; Nan, Sha; Li, Qiuhua; Ding, Mingxing; Ding, Yi (Frontiers in Microbiology, 2022)
Inflammatory lung injury is a common respiratory disease with limited therapeutic effects. Increasing opinions approved that prevention is more important than drug treatment for inflammatory lung injury. Astragalus polysaccharides (APS) has multiple bioactivities including anti-inflammation and immunoregulation. However, its preventive effects on inflammatory lung injury remain unclear. In this study, mice were pretreated with APS via intragastric gavage and then were intratracheally instilled with LPS to determine the role of APS in preventing lung injury. The results showed that APS pre-treatment improved the pathological changes of lung tissues, reduced the neutrophils infiltration, and inhibited the LPS-induced inflammation. Increasing evidence confirmed the close relationship between intestinal microbiota and lung inflammatory response. 16S rRNA analysis showed that APS treatment changed the microbiota composition in colon, increased the abundance of SCFAs-producing genus such as Oscillospira, Akkermansia and Coprococcus. Also, APS treatment significantly increased the serum concentrations of short-chain fatty acids (SCFAs) including butyrate and propionate, and their anti-inflammation effects were demonstrated on mice primary alveolar macrophages. Our data confirmed the preventive effects of APS on LPS-induced lung injury, which were partly contributed by the alteration of intestinal microbiota composition and the resulting increase of serum SCFAs.